Hubungan Penyesuaian Diri dengan Stres Akademik dalam Menjalani Pembelajaran Tatap Muka Terbatas Di Era New Normal Siswa Pada Sekolah Menengah Atas - Syaninda Putri Asyifa Siregar; Rahmulyani Rahmulyani (Medan State University, 2022)
The purpose of this study was to determine the relationship between adjustment and academic stress in limited face-to-face learning for class XI IPS students at SMA N 1 Lubuk Pakam for the Academic Year 2021/2022. The method in this study is a quantitative method. The research population is the students of class XI IPS. Sampling in this study using purposive sampling by taking a sample of 88 students who are stressed. Data collection was carried out using a questionnaire. The validity and reliability of the instrument was obtained by product moment correlation. Hypothesis testing using Pearson's product moment formula with the help of SPSS for Windows. The results of the analysis showed r = 0.661 and Rsquare = 0.437 and a significant value of 0.000 (p <0.05). Based on these results, the research hypothesis was put forward: